Screening of liquid organic hydrogen carriers (LOHCs) structures and analysis of economic viability of their implementation - Lim, Ngee Jhin (Nanyang Technological University, 2023)
The use of Liquid Organic Hydrogen Carriers (LOHC) allows for the realization of long-distance transport and long-term storages of hydrogen by loading hydrogen onto liquid carriers that can be transported and shipped in similar fashion to traditional fuels. Therefore, the use of a LOHC hydrogen value chain provides a viable basis for an intercontinental energy trade. Currently, there are many different promising LOHC systems being researched and developed, with the focus on finding a practical LOHC system with desirable characteristics like high storage capacities, compatibility with existing fuel infrastructure and low costs of hydrogenation and dehydrogenation. The main challenge to the economic feasibility and the practicality of an LOHC value chain is in the dehydrogenation phase due to the intensive energy input required for the dehydrogenation reaction to release stored hydrogen from the LOHC. The first part of this paper is focused on the dehydrogenation phase of the hydrogen value chain, investigating the relationship between the chemical structure and the equilibrium conversion, and the enthalpy of dehydrogenation of different LOHC systems. In the second half, an economic analysis was performed to assess the potential value of hydrogen energy to consumers. The following attributes in an LOHC which favor higher equilibrium conversions and correspondingly higher yields for dehydrogenation, were shown to be: 1) molecules with a ring structure, 2) containing heteroatoms (Heterocyclic compound), 3) having only one heteroatom and 4) functionalized ring structure with a hydrocarbon group. From these characteristics, the LOHC system that is favored is the H12-N-ethyl carbazole/H0-N-ethyl carbazole system. The results also showed that between heterocyclic and homocyclic compounds, the enthalpy of dehydrogenation was lower in the former group. The economic analysis gave the optimal dehydrogenation temperatures and the net value of hydrogen imports for each LOHC system. The calculated net value to import a kg of hydrogen under different LOHC systems were calculated, with the following results: 1-Methylperhydro Indole (2.70 – 3.80 USD/kg H2), 2-Methylperhydro Indole (2.87 – 3.97 USD/kg H2), Ammonia (0.88 – 2.28 USD/kg H2), Cyclohexane (1.48 – 2.58 USD/kg H2), Decalin (1.90 – 3.00 USD/kg H2), Ethane (-7.22 – -5.82 USD/kg H2), Formic Acid (5.80 – 7.20 USD/kg H2), H12-BT (1.91 – 3.01 USD/kg H2), H12-NEC (3.08 – 4.18 USD/kg H2), H18-DBT (1.83 – 2.93 USD/kg H2), Methylcyclohexane (1.64 – 2.74 USD/kg H2), Perhydro-Phenazine (2.30 – 3.40 USD/kg H2), Propane (-5.68 – -4.28 USD/kg H2). This gives information on potential savings when adopting hydrogen-based energy from different LOHC systems when compared to the current energy mix, as well as indications on potential economic feasibility of different LOHC systems.